Implementation of flipped classroom learning to increase students' learning independence in terms of students' cognitive style - Pratidiana, Deni; Yunitasari, Ika (Jurnal Riset Pendidikan Matematika, 2026)
The purpose of this study was to examine the effect of the flipped classroom learning model on students' learning independence based on students' cognitive styles. One category of student cognitive style is field-dependent and field-independent. This study examined the effect of the flipped classroom learning model on students' learning independence in terms of students' cognitive style. In this study, the experimental class treatment used the flipped classroom learning model, and the control class treatment used the scientific learning model. This type of research is quasi-experimental with a cluster random sampling technique. The subjects in this study were grade XI students of MA Malnu Pusat Menes in Pandeglang City. The results showed that: 1) the improvement of students' learning independence ability in the flipped classroom class is higher than in the scientific class, 2) the improvement of field independent students' learning independence ability in the flipped classroom class is higher than the control class, and 3) the improvement of field dependent students' learning independence ability in the flipped classroom class is higher than the control class.